2008
DOI: 10.1074/jbc.m708444200
|View full text |Cite
|
Sign up to set email alerts
|

The Layered Structure of Human Mitochondrial DNA Nucleoids

Abstract: Mitochondrial DNA (mtDNA) occurs in cells in nucleoids containing several copies of the genome. Previous studies have identified proteins associated with these large DNA structures when they are biochemically purified by sedimentation and immunoaffinity chromatography. In this study, formaldehyde cross-linking was performed to determine which nucleoid proteins are in close contact with the mtDNA. A set of core nucleoid proteins is found in both native and cross-linked nucleoids, including 13 proteins with know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
353
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(379 citation statements)
references
References 72 publications
17
353
0
4
Order By: Relevance
“…The finding that TFAM is very abundant is consistent with several other reports, demonstrating one TFAM molecule per 10 to 20 bp of mtDNA (13)(14)(15). In addition, biochemical characterization of purified nucleoids has shown that TFAM is the main protein component (20). TFAM is thus likely the main factor packaging and organizing mtDNA into nucleoids, but this finding does not exclude that other proteins may also be of importance.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The finding that TFAM is very abundant is consistent with several other reports, demonstrating one TFAM molecule per 10 to 20 bp of mtDNA (13)(14)(15). In addition, biochemical characterization of purified nucleoids has shown that TFAM is the main protein component (20). TFAM is thus likely the main factor packaging and organizing mtDNA into nucleoids, but this finding does not exclude that other proteins may also be of importance.…”
Section: Discussionsupporting
confidence: 81%
“…Confocal microscopy has shown that mtDNA and TFAM colocalize in mammalian cells and are present in punctuate aggregates corresponding to nucleoids (18,19). A large number of putative nucleoid proteins have been identified by using biochemical approaches to identify proteins that can be cross-linked to or copurified with mtDNA (20) or that colocalize with mtDNA on confocal microscopy (18,19). Association of a protein that is essential for mtDNA maintenance with mtDNA does not necessarily mean that it has a role in structural organization of the nucleoid.…”
mentioning
confidence: 99%
“…It has been suggested on the basis of immunofluorescent microscopy [32] and nucleoid massspectrometry analysis (see [33,34] for a recent overview) that nucleoids might organize so as to locally facilitate nucleoid maintenance and organize transcription, translation and biogenesis in its immediate surroundings. This also forms the basis for the suggestion that each nucleoid has a limited sphere of influence that could result in a focal mitochondrial OXPHOS deficiency if it contains mutant mtDNA [35].…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian nucleoid composition has been analyzed by several groups (30,31) and a common component identified is h-mtTFA, which is thought to be a major packaging component in addition to a transcription factor (32). However, in yeast and mammals, nucleoids are also associated with other proteins (33)(34)(35)(36) and exist as heterogeneous populations (35,36). At present differential nucleoid structure and function are poorly understood, but it is reported that only specific subsets of nucleoids (or mtDNA molecules) are undergoing transcription and replication at a given point in time (28,37,38).…”
mentioning
confidence: 99%